Green Infrastructures and the Architectural Design of Linear Parks: A Review - Rigolo, Fernanda Nascimento; Okimoto, Fernando Sergio (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective - The objective of this work is to analyze green infrastructures applied to sustainable urban drainage, highlighting their contribution to mitigating urban impacts such as floods, inundations, and heat islands, and their relation to urban planning and environmental management. Methodology - The research adopts a theoretical approach based on a literature review, exploring international models and discussing the relationship between urbanization and environmental management, focusing on the application of nature-based solutions in Brazilian cities. Originality/Relevance - The study fills a theoretical gap by exploring green urban drainage solutions in Brazilian cities, considering the current limitations in the implementation of these strategies. Its academic relevance lies in proposing innovation in sustainable urban planning. Results - The main results indicate that green infrastructure significantly contributes to water infiltration, flood reduction, and urban microclimate regulation, promoting climate resilience and environmental quality in cities. Theoretical/Methodological Contributions - This study offers a theoretical contribution by integrating the concepts of green infrastructure and urban drainage, as well as proposing innovative methodological approaches for the practical application of these concepts in urban planning. Social and Environmental Contributions - Social and environmental implications include promoting more resilient, sustainable cities with improved quality of life, as well as greater ecological connectivity, benefiting urban populations and the environment.